LEFT MOVEMENT IN YOGYAKARTA IN 1950-1965 - Wicaksono, Galih Agung (Kementerian Pendidikan dan Kebudayaan, 2020)
The national tragedy in 1965 claimed many victims, either parties related to the Movement of September 30th or their families. Yogyakarta is one of slaughtering acts of